Rethinking tropical phenology: insights from long-term monitoring and novel analytical methods - Morellato, Leonor Patrícia Cerdeira [UNESP]; Abernethy, Katharine; Mendoza, Irene [UNESP] (Wiley, 2018)
Here, we introduce the Special Section (SS) on long-term monitoring and new analytical methods in tropical phenology. The SS puts together nine original papers plus a synthesis, bringing significant advances and new insights into our understanding of tropical phenology across Africa and tropical America. The papers address environmental cues, methodological shortcomings, and provide innovative analytical approaches, opening new pathways, perspective and applications of tropical phenology for forest management and environmental monitoring. The SS is a substantial step toward a more comprehensive overview of trends in tropical phenology, as seven of nine studies evaluate >10-yr data sets applying new methods of analysis such as hierarchical Bayesian models, generalized additive models, and Fourier analysis. We argue that it is essential to maintain ongoing monitoring programs and build a tropical phenology network at least for long-term (>10 yr) study sites, providing the means for national and international financial support. Cross-continental comparisons are now a primary goal, as we work toward a global vision of trends and shifts in tropical phenology in the Anthropocene.
Keywords: America tropical; climate change; cross-continental comparison; flowering; fruiting; leafing; savanna; tropical Africa; tropical long-term patterns